An Analysis of Project-Based Learning Activities in Enhancing Students’ Speaking Ability in EFL Classroom - Arimbi Pamungkas; Rahayu Soraya; Sulistianah; Tri Dewantari (JURNAL ILMU PENDIDIKAN, 2026)
This study aimed to analyzed project-based learning activities in enhancing students’ speaking ability in EFL Classroom. This study used mixed methods research design. This study conducted at first semester students of Early Childhood Education Teacher Training STKIP Al Islam Tunas Bangsa. The participant consists of 35 students majoring in Early Childhood Education Teacher Training. Data collection techniques in this study used by the result of students’ project in speaking skill, observation, and interviews. The finding reveals that project-based learning activities in teaching speaking can improve students’ speaking skills. This is evident from the marks students received for presenting the projects students had created. The results showed that 40% of students received an A, 31.43% received a B, 20% received a C and 8.57% received a D. Furthermore, the result of the observation and interview reveals that there is an impact of students’ grammatical, vocabulary, fluency, creativity, and collaboration by using project-based learning activity and some challenges in enhancing students’ speaking ability in EFL Classroom by using project-based learning activity such as students’ grammatical, students’ lack of vocabulary, lack of self-confidence, the difficulties in pronunciation, and less motivation. it can be concluded that project-based learning activities in enhancing students’ speaking ability in EFL Classroom